Rus Africum IV : Lo Scavo Stratigrafico e I Materiali. - De Vos Raaijmakers, Mariette (Archaeopress Roman Archaeology Ser., 2019)
Aïn Wassel is the only rural site of Africa Proconsularis which has been excavated using the stratigraphic method and the detailed results are published in this volume thanks to an archaeological field survey of the surrounding rural region.